A modification of reference strain approach for thin-walled submarine pipelines under large-scale plastic strain and internal pressure. (July 2019) - Zhao, Xiaoxin; Xu, Lianyong; Jing, Hongyang; Han, Yongdian; Zhao, Lei; Cao, Jun; Lv, Yi; Song, Zhengrong
Abstract: Thin-walled pipelines are widely used in submarine oil and gas transportation. During the process of reel-lay and service, pipelines are subjected to large-scale plastic strain and internal pressure. Reference strain approach takes advantage of natural strain-controlled boundary condition directly. However, it is only reliable for small cracks by the assumption of equality between the reference strain and nominal strain. The effect of internal pressure is not considered in traditional failure analysis diagram (FAD). In this study, a theoretical solution of reference strain considering the influence of internal pressure is proposed. A corresponding failure assessment curve (FAC-New) considering the influence of internal pressure is also constructed based on the derived nominal strain. The proposed FAC-New is in contrast with FAC-R6. It is proved that FAC-New presents a more explicit classification of the influence of internal pressure in Engineering Critical Assessment (ECA). Highlights: A modified reference strain approach considering severe cracks is proposed. A new form of FAC considering the influence of internal pressure is proposed. A more accurate theoretical solution of reference strain is proposed. Pipe and crack geometries combined with material properties are considered.